Urban Economic Resilience and Supply Chain Dynamics: Evaluating Monetary Recovery Policies in Global Cities during the Early COVID-19 Pandemic - Jin Li; Guie Fu; Xichen Zhao (Mathematics, 2024)
The COVID-19 pandemic has profoundly impacted global economies, underscoring the urgency of deriving lessons to enhance future crisis preparedness. This study explores the effects of monetary recovery policies on supply chain dynamics across key global cities during the pandemic’s initial phase, emphasising policy interactions, industry engagement, and economic resilience. Utilising principal component analysis (PCA), data envelopment analysis (DEA), and tobit regression, we present a pioneering method to unravel the complex relationship between economic policies and urban supply chains. PCA simplifies data complexity and reveals complex policy-resilience relationships, while DEA facilitates a comparative efficiency analysis. Our findings underscore the critical importance of supply chain resilience in fostering early economic recovery, indicating that cities implementing diverse, sector-specific policies achieved more notable improvements in gross domestic product (GDP). This research not only advances methodological approaches for policy evaluation but also provides valuable insights for optimising urban economic recovery strategies amidst global challenges.